2014
DOI: 10.1042/cs20140180
|View full text |Cite
|
Sign up to set email alerts
|

NOD1 receptor is up-regulated in diabetic human and murine myocardium

Abstract: We demonstrate that the myocardium from murine models of diabetes and the myocardium of patients with Type 2 diabetes overexpress the receptor of the innate immune system NOD1. This up-regulation occurred in cardiomyocytes and was associated with an increased apoptotic profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 56 publications
1
13
0
1
Order By: Relevance
“…So far, only a limited number of studies in vivo have shown the effect of NOD1 in the cardiovascular field (23)(24)(25)(26). Consistent with a previous report (27), we here establish that Nod1 deficiency prevents early atherosclerosis development in Apoe 2/2 mice.…”
Section: Discussionsupporting
confidence: 92%
“…So far, only a limited number of studies in vivo have shown the effect of NOD1 in the cardiovascular field (23)(24)(25)(26). Consistent with a previous report (27), we here establish that Nod1 deficiency prevents early atherosclerosis development in Apoe 2/2 mice.…”
Section: Discussionsupporting
confidence: 92%
“…164 In addition, NOD1 expression is upregulated in heart tissues and cardiomyocytes of mice with T2DM, implying a possible role of NOD1 in diabetic cardiomyopathy. 165 ALRs are one of the newly characterized superfamilies of PRRs that recognize endogenous and exogenous DNA, such as poly (dA-dT) and vaccinia virus double stranded DNA. [167][168][169] Functionally, ALRs regulate inflammasome assembly, and cell differentiation, proliferation, and apoptosis.…”
Section: Nlrs In Diabetic Cardiomyopathymentioning
confidence: 99%
“…Nucleotide oligomerization-binding domain 1 (NOD1) is an innate immune receptor that is involved in the pathogenesis of diabetes in various organs, including the heart. Although increased NOD-1 is associated increased levels of NF-κB and apoptosis in diabetic mice, its underlying contribution still remains poorly understood [71]. NOD1 is found in cardiac fibroblasts, with levels increased in cardiac fibroblasts from Lepr db/db mice compared to non-diabetic controls [72].…”
Section: Nucleotide Oligomerization-binding Domainmentioning
confidence: 99%